Numerical Study of Mixed Convection Heat Transfer in Methanol based Micropolar Nanofluid about a Horizontal Circular Cylinder. (November 2019) - Swalmeh, M Z; Alkasasbeh, H T; Hussanan, A; Mamat, M
Abstract: In this article, the mixed convection boundary layer flow about a horizontal circular cylinder with a micropolar nanofluid, which is maintained at a constant surface heat flux, has been investigated. Three types of nanoparticles with distinct conductivities, namely, graphene oxide, copper and copper oxide are considered and suspended in methanol based micropolar nanofluid. The governing equations are transformed into nonlinear PDEs by applying the similarity transformations and then solved numerically by an implicit finite difference scheme known as Keller-box method. The results for the local wall temperature, local skin friction coefficient, temperature, velocity and angular velocity are plotted and discussed for different parameters such as nanoparticles volume fraction and mixed convection parameter in view of thermo-physical properties of nanoparticles and base fluid. Moreover, numerical results for the local wall temperature and local skin friction coefficient are obtained. It is found that copper (Cu) suspended methanol based micropolar nanofluid have higher velocity than the copper oxide (CuO) or graphene oxide (GO) methanol based micropolar nanofluid. Comparison have been made with published results on Newtonian fluid under special cases and obtained in close agreement.